An experimental investigation of the responses of classic spar platform subjected to bi-directional waves - Kurian, V.J. (Maxwell Science Publications, 2015)
The effect of the bi-directional short-crested waves on the dynamic motion responses of the moored classic spar is demonstrated from the results of the models test in this study. Practically in the design of offshore structures, long-crested or 2-dimensional wave properties that propagated to one direction are considered. Even though such long-crested wave is widely used for the design purposes, it is hardly determined in the real sea. The wind generated sea state in the real sea conditions are indeed well represented by the short-crested waves. Short-crested waves are defined as linear summation of long-crested wave series that propagated to different directions. Hence, the motions of the model were investigated experimentally by conducting the wave tank tests in the wave tank of Offshore Laboratory of Universiti Teknologi PETRONAS. Five groups of bi-directional wave series were defined and exerted on the classic spar model, which fabricated by using steel with scaling factor of 1:100. From the results measured, it was found that similar trends of the responses in term of Response Amplitude Operator (RAO) for surge, heave and pitch motions were obtained. Maximum responses of surge, heave and pitch were found due to wave crossing angle 90°, while minimum response was found due to wave crossing angle 135°, respectively. It could be concluded that the wave crossing angle 90° (BD3) gives the widest spreading for short crested waves, while the wave crossing angle 135° (BD4) gives the narrowest spreading for short crested waves. © Maxwell Scientific Organization, 2015.